Mapping media in China : region, province, locality - Sun, Wanning, 1963-; Chio, Jenny (Routledge contemporary China series, 2012)
Mapping Media in China is the first book-length study that goes below the 'national' scale to focus on the rich diversity of media in China from local, provincial and regional angles. China's media has played a crucial role in shaping and directing the country's social and cultural changes, and whilst these shifts have often been discussed as a single and coherent phenomenon, this ignores the vast array of local and regional variations within the country's borders. This book explores media as both a reflection of the diversity within China and as an active agent behind these growing difference.